(untitled) (Research, Society and Development, 2022)
Ending relationships are often complicated and bring with them psychic suffering, so it is natural for the mind to develop some coping mechanisms to go through this period in a less painful way. Faced with this situation, this article had as its main point to be researched the plausible strategies so that it is possible to face grief after the end of a love relationship, and this topic is widely discussed in contemporary times, especially among young people, so the objective of this research was study about the stages of mourning in order to contextualize what are the processes that involve such a state, and also how to face such a moment, in addition to social, cultural and psychological factors that can influence the mourning process, using a bibliographic research of qualitative approach. In addition, among the platforms used to choose the material to be analyzed are google academic, scielo, pepsic and BVS. The results showed that mainly women are more likely to stagnate in one of the stages of grief, developing syndromes and suffering longer than men, given the cultural and social context in which they are inserted, but in compensation men can experience the feeling of emptiness and psychic suffering. with greater intensity since they use behavioral strategies such as mending relationships that do not satisfy them in order to direct feelings towards less lasting relationships based on sex, avoiding attachment. It is important to emphasize the importance that psychology has in analyzes on this topic.